2012
DOI: 10.1007/s10152-012-0319-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the suitability of a remotely operated vehicle (ROV) to study the fish community associated with offshore gas platforms in the Ionian Sea: a comparative analysis with underwater visual censuses (UVCs)

Abstract: The effectiveness of a remotely operated vehicle (ROV) to describe the fish communities of three gas platforms located offshore Crotone (Italy, Ionian Sea) was investigated by comparing its observations with underwater visual censuses (UVCs). The study was carried out at two depth layers (0-6 and 12-18 m). Moreover, the ROV was used to survey three deeper depth layers up to 76 m. Overall, the ROV surveys failed to give a truthful representation of the fish communities underestimating the number of species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…ROV footage generally underestimates fish densities in comparison with visual surveys (Andaloro et al 2013). To correct for this discrepancy, predator densities were calculated using each method in an overlapping region in the Dry Tortugas using visual surveys from 2012 and 2014, and ROV surveys from 2012 and 2013.…”
Section: Predator Density and Behaviormentioning
confidence: 99%
“…ROV footage generally underestimates fish densities in comparison with visual surveys (Andaloro et al 2013). To correct for this discrepancy, predator densities were calculated using each method in an overlapping region in the Dry Tortugas using visual surveys from 2012 and 2014, and ROV surveys from 2012 and 2013.…”
Section: Predator Density and Behaviormentioning
confidence: 99%
“…The recent technological enhancement of remotely-operated vehicles (ROVs), which takes advantage of high definition video and digital cameras, is improving the biodiversity assessment of fish and benthic invertebrates especially in natural and artificial complex habitats, where it is difficult to use traditional sampling gears [6,32,33,34,41,42] and in deep environments, where diving is logistically limited and the use of submersibles is very expensive. Moreover, direct observation methods allow assessment of behaviors and other attributes, albeit brief, that are otherwise unattainable.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were drawn by Andaloro et al . [41] and Consoli et al . [52] in artificial habitats (extractive platforms and shipwrecks) located in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in which fish abundance near 3 gas platforms was estimated with an ROV and compared with fish abundance estimated by scuba divers, Andaloro et al (2013) found that 9 taxa of small benthic species were reported in the diver surveys but none of those taxa were observed with the ROV. Small rockfishes <20 cm TL could not be identified to species during nearshore ROV surveys in the waters of southeast Alaska (Johnson et al, 2003), and Love et al (2009) suggested that densities of small fish taxa, such as the bluebanded goby (Lythrypnus dalli), could be underestimated in their HOV surveys.…”
Section: Discussionmentioning
confidence: 99%